2018
DOI: 10.1088/1741-2552/aae12f
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective particle swarm optimization for postoperative deep brain stimulation targeting of subthalamic nucleus pathways

Abstract: These results suggest that pathway targeting with patient-specific model-based optimization algorithms can efficiently identify non-trivial electrode configurations for enhancing activation of clinically relevant pathways. However, the results also indicate that inter-pathway correlations can limit selectivity for certain pathways even with directional DBS leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 87 publications
1
30
0
Order By: Relevance
“…We also found that rotating the directional leads about their axis had no significant impact on performance variability (data not shown). Pena et al (2018) reported similar findings in their study of optimization algorithms for directional leads. With a constant configuration of active electrodes they observed less than 10% variation in activation across a 360° rotation of the lead about its axis.…”
Section: Discussionsupporting
confidence: 70%
“…We also found that rotating the directional leads about their axis had no significant impact on performance variability (data not shown). Pena et al (2018) reported similar findings in their study of optimization algorithms for directional leads. With a constant configuration of active electrodes they observed less than 10% variation in activation across a 360° rotation of the lead about its axis.…”
Section: Discussionsupporting
confidence: 70%
“…Recent algorithmic advances combine electrodes with different contact geometries, including cylindrical and directional leads, and patient specific models, including tissue anisotropy, to best target the sub-thalamic nucleus (STN) (Anderson et al, 2018). A multi-objective particle swarm optimization technique to select a combination of stimulation electrodes was found to be more effective than a single monopolar electrode in targeting the desired efferents from the STN (Peña et al, 2018). As ECoG electrodes become smaller and more numerous, algorithmic techniques such as the ones described above and more advanced ones based on artificial neural networks (Rao, 2019) would enable precisely targeted DES with the right combination of electrodes.…”
Section: Enabling Technologiesmentioning
confidence: 99%
“…Modeling studies and preclinical studies have shown that stimulation through a segmented electrode allows for steering current axially toward the therapy target, while avoiding regions that produce side effects. Pilot studies using segmented DBS leads have demonstrated the ability to improve outcomes by allowing clinicians to customize and shape stimulation to individual patient's anatomy .…”
Section: Introductionmentioning
confidence: 99%